Comparative Analysis of Students' Biology Learning Outcomes: Memory and Understanding Aspects - Yanti Yusipa (Journal of Academic Biology and Biology Education, 2024)
Purpose of the study: This research aims to analyze the learning outcomes of 11th-grade students by examining how they answer questions using memory aspects, evaluate the overall learning outcomes of the class, and identify the differences in learning outcomes between students who use memory aspects and those who use comprehension aspects to solve questions. Methodology: This study is a true experimental study. The population in this study were all students of Public High School 6 South Bengkulu totaling 142 people. The sample was taken using a random sampling technique of 42 people was obtained. This study used a learning outcome test instrument in form of multiple choice questions. Data analysis techniques used include descriptive statistics and inferential statistics. Main Findings: The analysis shows that students' abilities are in the moderate category. Biology learning outcomes are in the high category. The results of the hypothesis test show that the significance value is less than 0.05, so Ho is rejected and Ha is accepted, which means that there is a significant difference in the learning outcomes of class XI science students at Public High School 6 South Bengkulu who use memory and understanding aspects in answering questions. Novelty/Originality of this study: This type of study can provide valuable insights into the effectiveness of both cognitive abilities in understanding and remembering information in the context of learning Biology subjects. In addition, this study can also provide information to educators about more effective ways to help students learn and remember subject matter better.